Hybrid Fuzzy PI-Control Scheme for Quasi Multi-Pulse Interline Power Flow Controllers Including the P-Q Decoupling Feature - Vural, Ahmet Mete; Bayindir, Kamil Cagatay (KOREAN INST POWER ELECTRONICS, 2012)
Real and reactive power flows on a transmission line interact inherently. This situation degrades power flow controller performance when independent real and reactive power flow regulation is required. In this study, a quasi multi-pulse interline power flow controller (IPFC), consisting of eight six-pulse voltage source converters (VSC) switched at the fundamental frequency is proposed to control real and reactive power flows dynamically on a transmission line in response to a sequence of set-point changes formed by unit-step reference values. It is shown that the proposed hybrid fuzzy-PI commanded IPFC shows better decoupling performance than the parameter optimized PI controllers with analytically calculated feed-forward gains for decoupling. Comparative simulation studies are carried out on a 4-machine 4-bus test power system through a number of case studies. While only the fuzzy inference of the proposed control scheme has been modeled in MATLAB, the power system, converter power circuit, control and calculation blocks have been simulated in PSCAD/EMTDC by interfacing these two packages on-line.
Keywords: Decoupled power flow control; FACTS; Hybrid fuzzy-PI controller; Interline power flow controller (IPFC); Multi-pulse converter; Simplex method